Mental Workload Evaluation in Adaptive Boss Battle Gamification for PHP Programming Education: A Two-Phase NASA-TLX Analysis - Dimas Wahyu Wibowo; Aryo Wahyu Nugroho; Eka Larasati Amalia; Venny Meida Hersianty (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2026)
Programming education, particularly server-side PHP, imposes high cognitive demands through complex syntax and abstract logic, while conventional instruction often fails to sustain engagement, motivating gamification as an alternative. This study evaluates student mental workload in CodeBossArena, an adaptive Boss Battle gamification system developed with the ADDIE model. An adaptive pre-test classifies students into Easy, Medium, or Hard Boss Battles, supported by five gamification elements (XP, Badges, Leaderboard, Progress Bar, and a Countdown Timer). The core contribution is a two-phase workload comparison, diagnostic pre-test versus adaptive gamified intervention, rather than gamification or NASA-TLX individually. Workload was measured with the Raw NASA-TLX across two phases. Thirty-six students from Politeknik Negeri Malang participated: an Adaptive Group (n=26) at system-recommended difficulty and an Independent Group (n=10) who self-selected an easier level. Shapiro-Wilk tests guided paired t-test or Wilcoxon selection. The Adaptive Group showed a significant TLX Total increase from Phase 1 (M=62.63) to Phase 2 (M=68.27); t(25)=2.746, p=0.011, d=0.539. Temporal Demand changed most (W=8.0, p=0.0003, r=0.715), identifying the Countdown Timer as the dominant element, whereas the Independent Group showed no change (p=0.790), consistent with the adaptive mechanism. Badge acquisition was associated with lower frustration, and in-system logs indicated competency attainment per level. Because NASA-TLX measures perceived workload rather than engagement or learning, the latter remain to be confirmed in controlled studies.